Development of a structured clinical pharmacology review for specialist support for management of complex polypharmacy in primary care. Issue 7 (16th March 2020) - Threapleton, Christopher J.D.; Kimpton, James E.; Carey, Iain M.; DeWilde, Stephen; Cook, Derek G.; Harris, Tess; Baker, Emma H.
Abstract : Aims: Polypharmacy is widespread and associated with medication‐related harms, including adverse drug reactions, medication errors and poor treatment adherence. General practitioners and pharmacists cite limited time and training to perform effective medication reviews for patients with complex polypharmacy, yet no specialist referral mechanism exists. To develop a structured framework for specialist review of primary care patients with complex polypharmacy. Methods: We developed the clinical pharmacology structured review (CPSR) and stopping by indication tool (SBIT). We tested these in an age‐sex stratified sample of 100 people with polypharmacy aged 65–84 years from the Clinical Practice Research Datalink, an anonymised primary care database. Simulated medication reviews based on electronic records using the CPSR and SBIT were performed. We recommended medication changes or review to optimise treatment benefits, reduce risk of harm or reduce treatment burden. Results: Recommendations were made for all patients, for almost half (4.8 ± 2.4) of existing medicines (9.8 ± 3.1), most commonly stopping a drug (1.7 ± 1.3/patient) or reviewing with the patient (1.4 ± 1.2/patient). At least 1 new medicine (0.7 ± 0.9) was recommended for 51% patients. Recommendations predominantly aimed to reduce harm (44%). There was no relationship between number of recommendations made and time since last primary care medication review. We identified a core set of clinical information and investigations (polypharmacy workup) that could inform a standard screen prior to specialist review. Conclusion: The CPSR, SBIT and polypharmacy workup could form the basis of a specialist review for patients with complex polypharmacy. Further research is needed to test this approach in patients in general practice.